2013
DOI: 10.1016/s0254-6272(13)60166-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electroacupuncture and Chinese kidney-nourishing medicine on polycystic ovary syndrome in obese patients

Abstract: Acupuncture combined with medicine is better than just electroacupuncture for obese PCOS patients by improving obesity-related indexes, insulin sensitivity, and APN level. This indicates that acupuncture-medicine therapy is worth clinical popularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Studies in this field pointed out effective reduction of PCOS-induced hyperandrogenism due to low-frequency EA (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in this field pointed out effective reduction of PCOS-induced hyperandrogenism due to low-frequency EA (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…According to the study of Yu et al (10), the mechanism of increased ovulation by EA is unknown. However, based on a hypothesis, the release of gonadotropin-releasing hormone (GnRH) decreases in PCOS due to reduced inhibition of beta-endorphine or increased sympathetic activity in the ovaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electroacupuncture (EA) is considered to be an effective alternative to conventional needle acupuncture, is valuable in patients with PCOS, is a therapy where fine needles are placed in the skin and underly muscle tissue at specific areas of the body, and then input current flow in the near human body bioelectricity. Yu and Liao randomized 67 cases of obese patients of PCOS to the combination group and control group, combination group was treated with EA and Tiankui capsule, and control group was only treated with EA [148]. Results showed that BMI, WHR, BW, and FINS decreased and ISI and APN were higher in the combination group than that in the control group (P < 0.01).…”
Section: The Utilization Of Acupuncture Combined With Herbal Medicinementioning
confidence: 99%
“…e combination treatment could better alleviate the symptoms and endocrine indices, insulin sensitivity, leptin, and APN levels, to improve the quality of life of women with PCOS. Overall, in recent ten years, many RCTs have proved that the combination of acupuncture and herbal medicine has positive impact on reproductive dysfunction, endocrine disorder, and abnormal glucolipid metabolism in PCOS [145,146,[148][149][150]. e possible mechanisms of action of acupuncture for PCOS are as follows: (i) lower high sympathetic nerve activity and regulate parasympathetic and sympathetic activity; (ii) regulate the central nervous system through the hypothalamus-pituitary-ovary (HPO) axis and hypothalamus-pituitary-adrenal (HPA) axis; (iii) modulate the metabolic system by modulating expression of genes related to IR, obesity, and sympathetic activity in skeletal muscle and adipose tissue [151][152][153].…”
Section: The Utilization Of Acupuncture Combined With Herbal Medicinementioning
confidence: 99%